HOW DO GOVERNMENT DIGITAL CONTENT, THEORY OF PLANNED BEHAVIOUR, AND TAX AWARENESS AFFECT TAX COMPLIANCE? - Vinny Stephanie Hidayat; Nunik Lestari Dewi; Johanes Felix Gunawan (Jurnal Bisnis dan Akuntansi, 2025)
In the digital era, the utilization of technology by the government is crucial in improving tax compliance, especially for the younger generation as prospective taxpayers. This study examines the effect of tax digital content disseminated through the official social media of the Directorate General of Taxes on students' attitudes, subjective norms, perceived behavioral control, tax awareness, and tax compliance. The Theory of Planned Behavior approach is used as a theoretical basis to analyze changes in tax behavior. The research also examines the factors that attract students' attention to the digital content, by considering the attention span aspect. The sample in this study were active accounting students at one of the universities in Bandung City, who were selected through purposive sampling method. The method used is descriptive and explanatory research, with hypothesis testing using the PLS-SEM test. The novelty of this study lies in the integration of government digital content analysis with a behavioral psychology approach as well as attention to the attentional aspects of young audiences, which have not been widely discussed in previous tax compliance studies. This study found a positive relationship between government social media usage and elements of theory of planned behavior, tax awareness, and tax compliance. The results of this study provide practical implications for the government in designing more effective and sustainable digital communication strategies to increase young people's tax awareness and compliance.